Age-specific income trends in Europe: The role of employment, wages, and social transfers - Bernhard Hammer; Sonja Spitzer; Alexia Prskawetz (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2021)
This study analyses age-specific differences in income trends in nine European countries. Based on data from National Accounts and the European Union Statistics on Income and Living Conditions, we quantify age-specific changes in income between 2008 and 2017 and decompose these changes into employment, wages, and public transfer components. Results show that income of the younger age groups stagnated or declined in most countries since 2008, while income of the older population increased. The decomposition analysis indicates that the main drivers of the diverging trends are higher employment among the older population and a strong increase in public pensions, especially for women.
Keywords: 330; Generational Economy; Income; Intergenerational Equity